Measles Inclusion‐Body Encephalitis: Neuronal Phosphorylated Tau Protein is Present in the Biopsy but not in the Autoptic Specimens of the Same Patient. (13th December 2015) - Maderna, Emanuela; Fugnanesi, Valeria; Morbin, Michela; Cacciatore, Francesca; Spinello, Sonia; Godani, Massimiliano; Zoia, Riccardo; Tagliavini, Fabrizio; Giaccone, Giorgio
Abstract: Tauopathies are sporadic or familial neurodegenerative diseases characterized by the accumulation of phosphorylated tau in neurons and glial cells and include encephalitis related to measles virus such as subacute sclerosing panencephalitis. We describe a 45‐year‐old woman, with a history of lymphoma treated with immunosuppressant therapy who underwent an open biopsy of the right frontal cortex for a suspect of encephalitis, and died 4 days later. The neuropathological assessment on the bioptic sample revealed edema, severe gliosis and microglial activation, with lymphomonocytic perivascular cuffing and neurons containing both nuclear and cytoplasmic eosinofilic inclusions that ultrastructurally appeared as tubular and curvilinear non‐membrane‐bound 12–18 nm structures, leading to the diagnosis of measles inclusion‐bodies encephalitis. The biopsy specimen showed several cortical neurons with intense perikaryal immunoreactivity for anti‐tau antibodies recognizing phosphorylated epitopes while on autoptic specimens no phosphorylated tau immunoreactivity was detected. Our findings suggest that in specific conditions biopsy‐derived human tau may be phosphorylated at sites that may result not phosphorylated in autopsy‐derived specimens, most likely caused by post‐mortem dephosphorylation.